Temporal Cortex Activation to Audiovisual Speech in Normal-Hearing and Cochlear Implant Users Measured with Functional Near-Infrared Spectroscopy - van de Rijt, Luuk P. H.; van Opstal, A. John; Mylanus, Emmanuel A. M.; Straatman, Louise V.; Hu, Hai Yin; Snik, Ad F. M.; van Wanrooij, Marc M. (Frontiers in Human Neuroscience, 2016)
Background Speech understanding may rely not only on auditory, but also on visual information. Non-invasive functional neuroimaging techniques can expose the neural processes underlying the integration of multisensory processes required for speech understanding in humans. Nevertheless, noise (from fMRI) limits the usefulness in auditory experiments, and electromagnetic artefacts caused by electronic implants worn by subjects can severely distort the scans (EEG, fMRI). Therefore, we assessed audio-visual activation of temporal cortex with a silent, optical neuroimaging technique: functional near-infrared spectroscopy (fNIRS). Methods We studied temporal cortical activation as represented by concentration changes of oxy- and deoxy-hemoglobin in four, easy-to-apply fNIRS optical channels of 33 normal-hearing adult subjects and 5 post-lingually deaf cochlear implant (CI) users in response to supra-threshold unisensory auditory and visual, as well as to congruent auditory-visual speech stimuli. Results Activation effects were not visible from single fNIRS channels. However, by discounting physiological noise through reference channel subtraction, auditory, visual and audiovisual speech stimuli evoked concentration changes for all sensory modalities in both cohorts (p<0.001). Auditory stimulation evoked larger concentration changes than visual stimuli (p<0.001). A saturation effect was observed for the audiovisual condition. Conclusions Physiological, systemic noise can be removed from fNIRS signals by reference channel subtraction. The observed multisensory enhancement of an auditory cortical channel can be plausibly described by a simple addition of the auditory and visual signals with saturation.